Isolation Identification and Characterization of Cyanide Tolerating LAB from Fermented Cassava Pulp Juice - Ergun, Merve; MISATI, EDWIN; Yekesso, Ademe (International Journal of Formal Sciences: Current and Future Research Trends, 2025)
Restricted Access.